Ideas from yesterday for University Education today (Foro de Educacion, 2018)
University education has adapted to the prevailing circumstances and that it is even proving to be an essential resource in the optimization of the reality. Otherwise, the university is a very important part of the social system in which it is, and the training of excellent professionals is a cardinal issue for the proper functioning of such a system. Yes it is, today various professional profiles, classics and currents, are demanded to be formed in the classrooms of our universities. However, that is not all, and depending on how you look at it, is not even the most important. However, at the same time and internationally speaking, we have also witnessed the emergence of concerns about the nature of this education, above all in relation to the personal, ethical, and civic development of today’s student populace. It is logical to think, that is not enough to train excellent professionals, indeed, reality shows that this is not enough when personal and ethical training is insufficient or does not live up to the current circumstance. The aim of this paper is to focus on this aspect, and in doing so it revisits a past in which essential philosophical ideas were being formulated, ideas which this paper argues are highly pertinent to the current reality.